Exploring Novel Dimensions of Burnout Among Malaysian Healthcare workers: A Qualitative Thematic Analysis - Suriya Kumareswaran Vallasamy (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Burnout among healthcare workers (HCWs) has gained increased attention in the post-pandemic landscape due to its profound implications on workforce sustainability and patient care quality. Existing burnout assessment tools, such as the Maslach Burnout Inventory, were developed for general occupational settings and often fail to capture the unique emotional and cognitive stressors specific to healthcare environments, particularly in low- and middle-income countries. This study aimed to explore previously underrecognized dimensions of burnout among Malaysian HCWs to inform the development of a healthcare-specific burnout assessment instrument. Method: A qualitative study was conducted using a semi-structured focus group discussion with four expert participants specializing in mental and occupational health. Data were manually transcribed and analyzed using the framework method. Coding was performed collaboratively to ensure reflexivity, consistency, and reliability. Result: Two overarching categories, emotional exhaustion and cognitive exhaustion were identified, encompassing 11 subthemes, including hopelessness, medical errors, and cognitive dissonance. Conclusion: Findings highlight the inadequacy of existing generic burnout tools and underscore the need for a tailored assessment framework that encapsulates the psychological complexity of HCW burnout, especially in resource-constrained settings.